2017
DOI: 10.18632/oncotarget.22337
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib is effective for treatment of advanced hepatocellular carcinoma

Abstract: As treatment options for hepatocellular carcinoma (HCC) are currently limited, we evaluated the efficacy and safety of oral apatinib, a VEGFR-2 inhibitor, on patients with advanced HCC. Twenty-two patients from Tianjin Medical University Cancer Institute and Hospital were enrolled for evaluation. Apatinib was administered at 500 mg/day or 250 mg/day continuously. Clinical endpoints were time to disease progression (TTP), overall survival (OS), and safety. The median TTP of treated patients was 10.4 months (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Though the tested and recommended dose of apatinib is 750–850 mg/day, there are retrospective studies and case reports that have demonstrated significant efficacy and safety at a lower dose of 250–500 mg/day. 29 , 36 However, further well-controlled studies are required to validate the benefit of altered dosing in HCC patients. Our study strengths included 1) no loss of patients at follow-up, and 2) being the first reported study from China comparing the effectiveness of these two antiangiogenic drugs in patients with intermediate or advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Though the tested and recommended dose of apatinib is 750–850 mg/day, there are retrospective studies and case reports that have demonstrated significant efficacy and safety at a lower dose of 250–500 mg/day. 29 , 36 However, further well-controlled studies are required to validate the benefit of altered dosing in HCC patients. Our study strengths included 1) no loss of patients at follow-up, and 2) being the first reported study from China comparing the effectiveness of these two antiangiogenic drugs in patients with intermediate or advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is the first approved front-line anti-tumor agents for advanced HCC 11 , 12 , 52 . Recently, some other molecular target agents, e.g., Regorafenib or apatinib, were also approved for advanced HCC treatment 53 , 54 . Although these molecular targeted agents bring new hope for patients with advanced HCC, the efficacy of these agents is still far from satisfying.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib, a small molecule kinase inhibitor, is considered as a better alternative for patients who were resistant to sorafenib treatment. A study conducted with a limited number of subjects (22 patients with HCC) showed that apatinib decreased the levels of the HCC biomarker α-fetoprotein, proving its effectiveness in the treatment of advanced HCC [208] However, the later phase III clinical trial, EVOLVE-1, conducted in patients with advanced HCC after sorafenib treatment or in patients with sorafenib intolerance, did not reveal a substantial difference in the overall survival rate when everolimus was given alone [209]. So far, as per the ClinicalTrials.gov website maintained by the National Library of Medicine at the National Institutes of Health, 334 findings have been identified on sorafenib and its use to treat early and advanced stages of HCC.…”
Section: Clinical Trialsmentioning
confidence: 99%